2002
DOI: 10.1081/erc-120016984
|View full text |Cite
|
Sign up to set email alerts
|

HOXGENE EXPRESSION IN ADULT TISSUES WITH PARTICULAR REFERENCE TO THE ADRENAL GLAND

Abstract: In comparison to the embryo, very little work has been carried out on the expression and role of Hox genes in the adult animal. An expression profile of all 39 vertebrate Hox genes on a select panel of adult human tissues reveals that in fact these genes are widely expressed throughout the adult human and a colinear pattern of expression is displayed similar to that of the developing embryo. Of particular interest is the abundance of Hox genes that are expressed within the adult adrenal gland. Adrenal cortical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…In adults, HOX genes continue to be expressed and thereby retain developmental plasticity in certain tissues or maintain homeostasis. However, there has been much less work on gene expression in adult tissues compared to developing tissues [45,46]. We showed that HOX gene expression in adult marsupial tissues was tissue-specific and differentially expressed (Figure  3).…”
Section: Discussionmentioning
confidence: 85%
“…In adults, HOX genes continue to be expressed and thereby retain developmental plasticity in certain tissues or maintain homeostasis. However, there has been much less work on gene expression in adult tissues compared to developing tissues [45,46]. We showed that HOX gene expression in adult marsupial tissues was tissue-specific and differentially expressed (Figure  3).…”
Section: Discussionmentioning
confidence: 85%
“…It is noteworthy that some of the HOX family genes (HOXA7, HOXA11, and HOXB9) are up-regulated in APA relative to AAG. A previous report demonstrated that 23 out of 39 HOX cluster genes are expressed in human adrenal glands and that HoxB2, B4, B5, and B9 are expressed in order from the capsule to the inner zona reticularis in the rat adrenal cortex (29). Because some HOX genes are involved in cellular differentiation and tumorigenesis (45), it is interesting to speculate that aberrant HOX gene activation contributes to tumorigenesis in APA.…”
Section: Discussionmentioning
confidence: 99%
“…We identified several genes that were up-regulated in APA that were not reported previously (Supplementary Table 4). These included the HOX gene family, which has been shown to play a crucial role in adrenal zonation (29). A heat map representation of the HOX gene family revealed increased expression of HOXA7, HOXA11, and HOXB9 in APA relative to AAG (Fig.…”
Section: Transcriptome Analysismentioning
confidence: 99%
“…Colinear expression of different HOX genes are crucial for proper cell differentiation and development (11, 12). In addition to their crucial roles in embryonic development, HOX gene appeared to play important roles in postnatal development (13). Various HOX genes such as HOXA5, HOXA7, HOXA10 etc are shown to be important for cell cycle regulation (14).…”
Section: Introductionmentioning
confidence: 99%